Comparison of once-daily versus twice-daily combination of Ropinirole prolonged release in Parkinson’s disease - Yun, Ji Young (BioMed Central, 2013)
BACKGROUND: Ropinirole prolonged release (RPR) is a once-daily formulation. However, there may be individual pharmacokinetic differences so that multiple dosing may be preferred in some individuals. This study compares once-daily and twice-daily RPR in patients with Parkinson’s disease. METHODS: This study was an open-label crossover study. We enrolled Parkinson’s disease patients on dopamine agonist therapy with unsatisfactory control such as motor fluctuation, dyskinesia and sleep-related problems. Agonists were switched into equivalent dose of RPR. Subjects were consecutively enrolled into either once-daily first or twice-daily first groups, and received the same amount of RPR in a single and two divided dosing for 8 weeks respectively in a crossover manner without a washout period. The primary outcome was a questionnaire of the preference completed by patients in the last visit. The secondary outcome measures included the Unified Parkinson’s Disease Rating Scale part 3 (mUPDRS), Hoehn and Yahr stage (H&Y); sleep questionnaire including overall quality of sleep, nocturnal off symptoms and early morning symptoms; Epworth Sleep Scale (ESS); compliances and patient global impression (PGI). RESULTS: A total of 82 patients were enrolled and 61 completed the study. 31 patients preferred twice-daily regimen, 17 preferred the once-daily regimen, and 13 had no preference. Their mean mUPDRS, H&Y, ESS, sleep quality, compliance and adverse events were not statistically different in both regimens. PGI-improvement on wearing off defined was better in twice-daily dosing regimen. CONCLUSIONS: RPR is a once-daily formulation, but multiple dosing was preferred in many patients. Multiple dosing of RPR might be a therapeutic option if once-daily dosing is unsatisfactory. TRIAL REGISTRATION: This study is registered with ClinicalTrials.gov, number NCT00986245.